Decompressive craniectomy 116 h after malignant middle cerebral artery infarction. Issue 7 (19th February 2016) - Yamaguchi, Hiroshi; Yamamoto, Kazuki; Akutsu, Nobuyuki; Kusumoto, Mayumi; Kajihara, Shinsuke; Yamaguchi, Yoshimichi; Takeda, Hiroki; Kawamura, Atsushi; Uetani, Yoshiyuki
Abstract: The optimal timing of decompressive craniectomy in pediatric patients after presentation with malignant middle cerebral artery infarction is unknown. We report herein the case of a previously healthy 6‐year‐old Japanese girl who had good outcome after emergency decompressive craniectomy 116 h after malignant middle cerebral artery infarction. This case suggests that the timing of decompressive craniectomy can be delayed until deterioration of neurological findings and, compared with adults, a more prolonged time course for surgical intervention might be acceptable.